Strengthening Legal Awareness of Consumer Protection and Standard Clauses for Micro Business Actors Through Community Service Activities - Suryaningsih, Suryaningsih; Purborini, Vivi Sylvia; Kasmin, Kasmin; Novitasari, Rika; Harsanti, Tikka Dessy (Abdimas Indonesian Journal, 2026)
Micro business actors frequently use standard clauses in consumer transactions without fully understanding their legal implications under Law No. 8 of 1999 on Consumer Protection. This low level of legal awareness may lead to the inclusion of unfair standard clauses that violate consumer rights and expose micro enterprises to potential legal risks. This community service activity aimed to enhance the legal awareness of micro business actors regarding consumer protection, particularly in relation to the lawful use of standard clauses in business contracts. The activity was implemented through legal counseling methods, including lectures, interactive discussions, and question-and-answer sessions. The materials covered consumer rights and obligations, prohibited standard clauses under consumer protection law, and the importance of balanced contractual relationships. The results showed a significant improvement in participants’ understanding and awareness, with approximately 70% of participants demonstrating increased knowledge of lawful standard clauses based on pre- and post-activity evaluations. This program is expected to encourage micro business actors to apply fair and legally compliant standard clauses, thereby supporting sustainable and equitable business practices.